Role of family communication patterns as predictors of behavioral health among students of public universities in north of Iran - Afsaneh Bakhtiari; Fatemeh Kashefi; Hajar Pasha; Fatemeh Nasiri-Amiri; Fatemeh Bakouei; Elnaz Saffari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Communication is one of the oldest and greatest human achievements and the basis of social life. The aim of this study was to evaluate the role of family communication patterns as predictors of behavioral health among students of public universities in the north of Iran. MATERIALS AND METHODS: In this cross-sectional study, a total of 461 students from all the public universities of Babol, Iran, were selected in 2019. A stratified sampling random method was used to select the samples. The demographic characteristics, Depression Anxiety Stress Scale, Acceptance and Action Questionnaire, Rosenberg self-esteem questionnaire, and Communication Skills Interpersonal Test were used to collect data. Simple and multi-variate linear regressions as well as Pearson's correlation coefficient were utilized for data analysis. RESULTS: The mean and standard deviation scores of conversation orientation and conformity orientation were 35.61 ± 0.55 and 19.31 ± 0.41, respectively. Family conversation orientation was a significant predictor of behavioral health scales of students (except for acceptance and action), predicting negatively and significantly depression, anxiety, stress, and positively self-esteem and inter-personal communication skills of students. Family conformity orientation was also a significant predictor of behavioral health scales (except for inter-personal communication skills) of students, which predicted positively and significantly depression, anxiety, stress, and negatively acceptance, action, and students' self-esteem. CONCLUSION: To prevent behavioral health problems, it is necessary to observe conformity orientation and rely on conversation orientation.